A novel 3D quantification technique for mucosa thickness / Rohana Ahmad and Mohamed Ibrahim Abu Hassan - Ahmad, Rohana; Abu Hassan, Mohamed Ibrahim (Research Innovation Business Unit, 2014)
The mucosa varies in thickness between regions of the mouth and a two-dimensional method of measurement by selecting a few points which was commonly done in the past may seriously misrepresent the actual thickness of the mucosa. The objective of this project is to quantify the thickness of mucosa in a three-dimensional manner and to allow clear visualization of the overall thickness as well as. Cone Beam Computerized Tomography (CBCT) images were taken of the edentulous patient with denture incorporated with barium sulphate in-situ. The denture allows clear delineation of the bone and soft tissue mucosa. A 3D model of the mucosa was calculated using a medical imaging program (Mimics) and subsequently exported to 3-matics for wall thickness analysis. The outcome of this project is a novel technique to quantify mucosa thickness in three dimensions which subsequently could be used to evaluate the effect of other parameters on bone such as masticatory pressure on resorption.